2012
DOI: 10.1016/j.ajhg.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Recessive HYDIN Mutations Cause Primary Ciliary Dyskinesia without Randomization of Left-Right Body Asymmetry

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder characterized by defective cilia and flagella motility. Chronic destructive-airway disease is caused by abnormal respiratory-tract mucociliary clearance. Abnormal propulsion of sperm flagella contributes to male infertility. Genetic defects in most individuals affected by PCD cause randomization of left-right body asymmetry; approximately half show situs inversus or situs ambiguous. Almost 70 years after the hy3 mouse possessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
219
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 266 publications
(229 citation statements)
references
References 56 publications
9
219
0
1
Order By: Relevance
“…While tremendous progress has been made in recent years in unveiling the molecular mechanisms of the disease [2,3,[8][9][10][11][12][13][14][15][16][17][18][19], PCD management is still hampered by a lack of fundamental data on epidemiology, clinical presentation, disease course and effects of different treatment strategies [4][5][6]. Patient registries are well-known tools to assemble sufficient numbers of individuals with a rare disease to assess and monitor patient data in a standardised and longitudinal way, and to recruit candidates for clinical research studies [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…While tremendous progress has been made in recent years in unveiling the molecular mechanisms of the disease [2,3,[8][9][10][11][12][13][14][15][16][17][18][19], PCD management is still hampered by a lack of fundamental data on epidemiology, clinical presentation, disease course and effects of different treatment strategies [4][5][6]. Patient registries are well-known tools to assemble sufficient numbers of individuals with a rare disease to assess and monitor patient data in a standardised and longitudinal way, and to recruit candidates for clinical research studies [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that mutations in genes affecting the central pair of microtubules can cause laterality abnormalities while mutations in genes affecting portions of the cilia other than the central pair do not affect laterality. 65,66 It is not only flow of embryonic fluid created by this rotary movement of cilia that affects laterality, however, but also impairment in ciliary sensory function. While the motile nodal cilia create the leftward flow of embryonic fluid, there is the requirement of downstream cilia to sense the flow, thus producing the co-called two-cilia hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, defects of nexin link components [63], central pair components [64], ciliary biogenesis defects [14] and defects caused by DNAH11 [65,66], usually cannot be visualized by classic TEM. Thus, normal ultrastructure cannot rule out PCD.…”
Section: Page 5 Of 36mentioning
confidence: 99%
“…Male patients with mutations in CCDC114 (coding for a docking protein for the ODA) are generally fertile [70]. Situs abnormalities are not observed in patients with mutations affecting the central pair [64] or radial spokes [49,50,69], nor in patients with reduced generation of multiple motile cilia [13,14]. However, it is likely that variable clinical pictures occur between patients with different mutations within a particular gene and even between patients with identical mutations.…”
Section: Genetics: Pcd Is Generally An Autosomal Recessive Disease Tmentioning
confidence: 99%